2019
DOI: 10.1021/acs.jpca.9b07235
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Partial Activation of Water by Open-Shell Interactions, Cl(H2O)1–4

Abstract: The partial chemical activation of water by reactive radicals was examined computationally for small clusters of chlorine and water, Cl • (H 2 O) n=1−4 . Using an automated isomer-search procedure, dozens of unique, stable structures were computed. Among the resulting structural classes were intact, hydrated-chlorine isomers, as well as hydrogen-abstracted (HCl)(OH)(H 2 O) n−1 configurations. The latter showed increased stability as the degree of hydration increased, until n = 4, where a new class of structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 145 publications
3
13
0
Order By: Relevance
“…This hemibonding-type configuration is surprisingly similar to configurations oberved in recently studied hydrated halogen-atom complexes. 60,61 Even with the correlation-related caveats discussed above, however, such an analysis yields a bit of a conundrum. These hemibonding interactions would be expected to be quite weak.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This hemibonding-type configuration is surprisingly similar to configurations oberved in recently studied hydrated halogen-atom complexes. 60,61 Even with the correlation-related caveats discussed above, however, such an analysis yields a bit of a conundrum. These hemibonding interactions would be expected to be quite weak.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Before proceeding to larger clusters, some aspects of the bonding at n = 4 that were not investigated in ref are first presented here. Shown in Figure are occupied molecular orbitals and their energy eigenvalues for isomers of each structural class ( 4A , 4D , and 4G ).…”
Section: Resultsmentioning
confidence: 99%
“…The isomer energies discussed in this section and those that follow have been computed with CCSD/aug-cc-pVDZ single points on BHHLYP/aug-cc-pVDZ structures. The previous analysis of smaller clusters demonstrated that the BHHLYP density functional performed particularly well for chlorine–water systems and often found conformers that other functionals neglected. The well-known problems of many density functionals when describing charge-transfer behavior nonetheless kept a healthy helping of skepticism simmering in the background of this investigation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Main geometrical parameters of the structures studied in this work, obtained at the CISD/MR-CISD level. Reference values are from: a ref ; b ref ; c ref ; d ref ; e ref ; f ref ; and g ref . For most of the structures, the aug-cc-pVTZ basis set has been used, while for Cl – (H 2 O) (the only exception) the d-aug-cc-pVTZ­(Cl)/aug-cc-pVTZ­(C,H,O) basis set has been used.…”
Section: Computational Detailsmentioning
confidence: 99%